Defining Long-term Outcomes With Living Donor Liver Transplantation in North America. Issue 3 (September 2015) - Olthoff, Kim M.; Smith, Abigail R.; Abecassis, Michael; Baker, Talia; Emond, Jean C.; Berg, Carl L.; Beil, Charlotte A.; Burton, James R.; Fisher, Robert A.; Freise, Chris E.; Gillespie, Brenda W.; Grant, David R.; et al.
Abstract : Objectives: To compare long-term survival of living donor liver transplant (LDLT) at experienced transplant centers with outcomes of deceased donor liver transplant and identify key variables impacting patient and graft survival. Background: The Adult-to-Adult Living Donor Liver Transplantation Cohort Study is a prospective multicenter National Institutes of Health study comparing outcomes of LDLT and deceased donor liver transplant and associated risks. Methods: Mortality and graft failure for 1427 liver recipients (963 LDLT) enrolled in the Adult-to-Adult Living Donor Liver Transplantation Cohort Study who received transplant between January 1, 1998, and January 31, 2014, at 12 North American centers with median follow-up 6.7 years were analyzed using Kaplan-Meier and multivariable Cox models. Results: Survival probability at 10 years was 70% for LDLT and 64% for deceased donor liver transplant. Unadjusted survival was higher with LDLT (hazard ratio = 0.76, P = 0.02) but attenuated after adjustment (hazard ratio = 0.98, P = 0.90) as LDLT recipients had lower mean model for end-stage liver disease (15.5 vs 20.4) and fewer received transplant from intensive care unit, were inpatient, on dialysis, were ventilated, or with ascites. Posttransplant intensive care unit days were less for LDLT recipients. For all recipients, female sex and primary sclerosing cholangitis were associated with improved survival, whereas dialysis and older recipient/donor age were associated with worse survival. Higher model for end-stage liver disease score was associated with increased graft failure. Era of transplantation and type of donated lobe did not impact survival in LDLT. Conclusions: LDLT provides significant long-term transplant benefit, resulting in transplantation at a lower model for end-stage liver disease score, decreased death on waitlist, and excellent posttransplant outcomes. Recipient diagnosis, disease severity, renal failure, and ages of recipient and donor should be considered in decision making regarding timing of transplant and donor options. Clinical Trials ID: NCT00096733. Abstract : Supplemental Digital Content is Available in the Text.This study investigated long-term outcomes in the Adult-to-Adult Living Donor Liver Transplantation Cohort Study cohort and compared results between living donor liver transplant (LDLT) and deceased donor liver transplant (DDLT). We identify factors associated with long-term patient and graft survival. LDLT provides significant sustained benefit compared with DDLT, and progression to higher severity of disease is prevented if the candidate is able to undergo LDLT at an earlier stage.